Implementation of Religious Moderation Values in Islamic Religious Education at Muslim Nusantara Al-Washliyah University and Al-Azhar Medan University (Multi-Site Approach) - Haidir, Haidir; Nasution, Wahyudin Nur; Mesiono, Mesiono (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to describe the implementation of religious moderation values in Islamic Religious Education learning at Al-Washliyah Nusantara Muslim University and Al-Azhar University Medan. This research uses qualitative research with a multi-site approach with a case study research method. This research was conducted using 2 (two) sites, namely site I at Al-Washliyah Muslim Nusantara University and site II at Al-Azhar University Medan. The data collection techniques used in this research were interview, observation, and documentation study. The results of this study indicate that the implementation of religious moderation values in learning Islamic Religious Education at Al-Washliyah Muslim Nusantara University and Al-Azhar University Medan has been implemented well but not yet perfect comprehensively. The implementation of religious moderation values is done by using insertion and optimization methods. The insertion method carried out by Al-Washliyah Muslim Nusantara University is in the form of applying 17 religious moderation lecture materials through the Islamic Religious Education course with a load of 6 credits, while for Al-Azhar University Medan it is done through 23 religious moderation materials with a load of 8 lecture credits. While the optimization method is carried out through learning activities such as the introduction of lectures, methods and media for learning PAI. The novelty of this research is that there is an application of religious moderation carried out through the insertion and optimization method at PTU.